Opsoclonus-myoclonus syndrome (Kinsbourne’s syndrome) - V. M. Alifirova; T. A. Valikova; N. V. Pugachenko; N. V. Kubar; M. N. Azhermacheva; N. B. Vershinina; S. D. Kazakov; E. S. Koroleva (Бюллетень сибирской медицины, 2020)
Kinsbourne’s syndrome or opsoklonus-myoclonus syndrome is an autoimmune disease of the central nervous system mainly affecting the cerebellum and its connections. The disease is characterized by progressive course and is rarely observed. There is no accurate data on the prevalence of opsoklonusmyoclonus syndrome in Russia. The etiology and pathogenesis of the disease are being studied. This disease can develop against the background of cancer, infectious diseases and vaccinations. The article presents a ñlinical case of this rare pathology.